BİLİM SANAT MERKEZLERİ PROGRAMLARINA YÖNELİK BEKLENTİLERİN İNCELENMESİ. - TORUNOĞLU, Hayriye; ÜNAL, Menderes (Erciyes Akademi, 2023)
This study aims to evaluate the programs implemented in Science and Art Centers according to the expectations of students, teachers and parents. The research was conducted with students, parents and teachers working in SACs in 5 different cities (Aksaray, Kırşehir, Kırıkkale, Nevşehir, Niğde) during the 2020-2021 and 2021-2022 academic years. The study was carried out with the case study method, one of the qualitative research methods. Typical sampling method, one of the purposeful sampling methods, was used to determine the research sample. The research data were obtained with the SAC Programs Evaluation Form prepared by the researcher. The MAXQDA program was used in the analysis of the data and the data were analyzed with the content analysis method. According to the results of the study; while students' expectations from BİLSEM programs are grouped under the headings of social development, academic success and personal development, parent expectations focus on academic development. It has been revealed that teachers have expectations from BİLSEM programs towards students and practice. It was observed that the expectations of the students were mostly met, and the expectations of the teachers for a rich content and flexible program were met. It was concluded that the expectations of the parents about contributing to the personal development of the students were met.